The Role of the Prophetic Sunnah in Promoting Inclusivity within Contemporary Educational Settings - Fikri, Muhammad 'Alimul; Purnama, Jumah; Basri, Basri (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
The Sunnah of the Prophets is extremely important in fostering awareness in Indonesia's contemporary educational environment. Emphasized the role of the Sunnah of the Prophet in promoting tolerance and awareness in the context of modern education. In this article, research is conducted using primary sources such as book summaries or other relevant sources, which are referred to as primary sources of research. Additionally, secondary sources are identified by analyzing data from journals, articles, books, websites, and various other sources related to the subject. The results of this study demonstrate how important it is to develop an inclusive learning environment that values diversity and respects individuality as well as how tolerance and hard work in the face of multiple traditions have contributed to the rise of inclusive education in Indonesia.